Data processing capability of polarization dynamics in ferroelectric-gate transistor-based physical reservoir computing - Yu Ukezeki; Sota Inoue; Norifumi Fujimura; Tokuji Yokomatsu; Kensuke Kanda; Kazusuke Maenaka; Kasidit Toprasertpong; Shinichi Takagi; Takeshi Yoshimura (Applied Physics Express)
We investigated the relationship between the polarization characteristics of ferroelectric Hf _0.5 Zr _0.5 O _2 thin-films and data processing capability in physical reservoir computing. Ferroelectric-gate field-effect transistors (FeFETs) with a metal-ferroelectric-metal-insulator-semiconductor structure were employed with varying area ratios between the ferroelectric capacitors and floating gate-electrodes. The voltage applied to the ferroelectric layers was theoretically calculated using load line analysis and determined experimentally. In a time-series prediction task, the FeFETs showed low error rates under conditions that produced multiple hysteresis loops in dynamic transfer waveforms. The results indicate that data processing capability is improved when a substantial portion of polarization is switched.